2010
DOI: 10.1148/radiol.09090583
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Reduced Radiation CT Protocols on the Detection of Renal Calculi

Abstract: Decreasing the tube charge from 100 to 30 mAs resulted in similar detection of renal stones while reducing patient radiation exposure by as much as 70%. Multidetector CT scanning parameters should be tailored to minimize radiation exposure to the patients while helping detect clinically significant renal stones.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(21 citation statements)
references
References 24 publications
0
21
0
Order By: Relevance
“…There have been studies on reduced-dose CT in cadavers in the United States and in small samples of selected populations outside the country. [12][13][14] These studies have also often excluded or found poor performance of nonsize-adjusted protocols in more obese patients, who are at increased risk for kidney stone and incur a higher radiation dose. 1,[15][16][17][18] Previous studies have also not followed patients receiving reduced-dose CT to determine its ability to predict outcomes and need for intervention.…”
Section: Background and Importancementioning
confidence: 99%
“…There have been studies on reduced-dose CT in cadavers in the United States and in small samples of selected populations outside the country. [12][13][14] These studies have also often excluded or found poor performance of nonsize-adjusted protocols in more obese patients, who are at increased risk for kidney stone and incur a higher radiation dose. 1,[15][16][17][18] Previous studies have also not followed patients receiving reduced-dose CT to determine its ability to predict outcomes and need for intervention.…”
Section: Background and Importancementioning
confidence: 99%
“…There are well-established practices of using low-dose CT in the detection of renal stone disease resulting in inherently ‘noiser’ images than in conventional CT examinations but without compromising diagnostic confidence for this clinical entity [3, 4]. In this article, we focus on the emergence of new iterative reconstruction techniques that have developed over the past few years.…”
Section: Introductionmentioning
confidence: 99%
“…These studies have consistently shown that low-dose CT provides a sensitivity and specificity >95 % and is similar to conventional CT for the detection of both renal and ureteral calculi [31,36,37]. Low-dose CT has also shown efficacy in detecting stone composition by measured Hounsfield units [38][39][40][41] and may assist in selecting the correct treatment regimen [42].…”
Section: Reducing Radiation During Work-up For Urolithiasismentioning
confidence: 84%